Development of the law protecting securities investors against market misconduct in the UK, Australia and Singapore - Loke, Alexander F. H.; Columbia University (2008)
This dissertation seeks to do a comparative study of the development of the law on market misconduct in three Anglo-Commonwealth jurisdictions with well developed markets: the UK, Australia and Singapore. Given that the subject jurisdictions have many common premises in English law, the researcher wanted to find out how the contours of legal protection have changed, and the issues disclosed therein. The First Article has been published as "From the Fiduciary Theory to Information Abuse: The Changing Fabric of Insider Trading Law in the UK, Australia and Singapore" 54 American Journal of Comparative Law 123-172 (2006). The article argues that while earlier insider trading laws of the subject jurisdictions may reveal the influence of the fiduciary theory in the fashioning of the law, they have since come to be shaped by a working out the tension between the parity of information norm and the economic efficiency noun.
The article examines how the contours of insider trading liability evolved in the UK, Australia and Singapore, and corollary to that, the ramifications for insiders, investors market professionals and persons associated with them. In their sophistication, these insider trading regimes easily match that of US federal securities law. From a comparative perspective, therefore, they offer attractive alternatives to the US model, particularly for common law jurisdictions whose legal cultures are closer to the Anglo-Commonwealth variety than the Anglo-American variety. The Second Article is "The Protected Interests in the Private Right of Action for Insider Trading: A Comparative Perspective" 7 Journal of Corporate Law Studies 307-335 (October 2007). The article is the first of a pair of articles examining the counterpart to regulatory protection of investor interest---the right of investors to sue for market misconduct.
The Third Article continues the analysis of the securities investor's right of action against market misconduct, in this instance market manipulative statements and conduct. The Article has been published as "The Investors' Protected Interest against Market Manipulation in the UK, Australia and Singapore" 21 Australian Journal of Corporate Law 22-50 (2007). The Fourth Article examines the evolution of the parameters that determine the prospect of securities class actions in the subject jurisdictions.
It is tentatively entitled "Actualizing Investors' Rights in England, Australia and Singapore". On the premise that securities investors typically hold small stakes and suffer losses that from an economic perspective are individually non-recoverable, the article examines two sets of issues that broadly underpin the likelihood of such small investors realizing their rights: first, whether the law provides an aggregating mechanism that allows for the ready institution of class action on behalf of investors, and second, the funding problem which include issues such as the lawyers' costs and disbursements, and adverse cost orders. (Abstract shortened by UMI.)
(UMI)AAI3305247
Source: Dissertation Abstracts International, Volume: 69-03, Section: A, page: 1132.
Adviser: John C. Coffee, Jr.
Thesis (J.S.D.)--Columbia University, 2008.
Microfiche.
Keywords: Law